Review on cross-chain technology research of blockchains - Chuannian SHEN (物联网学报)
With the in-depth development and continuous innovation of blockchain technology, blockchain networks suitable for different application scenarios and design requirements have emerged as the times require, the mutual independence of blockchains inevitably forms the value island effect of the blockchain.Cross-chain technology is an important technical means to realize industrial collaboration and value circulation between different blockchains and improve their interoperability and scalability.Firstly, the basic concept of cross-chain was introduced.And then, the technical difficulties of cross-chain, the technical characteristics of the main mechanism of cross-chain, and the security of cross-chain were analyzed in detail.Finally, the challenges faced by the current cross-chain technology were introduced, and the future development of cross-chain technology was prospected.